Benign Metastasizing Leiomyoma of the Uterus with Pulmonary and Bone Metastases - Parikshit Padhi; Margarita Topalovski (Hindawi Limited, 2021)
Benign metastasizing leiomyoma (BML) is a rare spindle cell neoplasm seen in middle-aged women who have a history of leiomyoma of the uterus. The most common sites of metastases are the lungs; however, other sites of spread have been documented. These tumors by definition have no malignant features on histology and tend to be estrogen and progesterone positive. We present a middle-aged woman who was incidentally found to have multiple pulmonary nodules and a mass on her sternum after she was involved in a motor vehicle accident. She had a history of uterine leiomyoma and had undergone a hysterectomy ten years prior to the accident. Biopsies were performed of the lung nodules and sternum mass and compared to her hysterectomy specimen, and they were identical, and hence, she was diagnosed with BML. Due to the growing tumor of her sternum, she was started on tamoxifen with stability of her tumors. These tumors, since they are benign, tend to have an indolent course. However, in the instances that treatment is warranted, options include surgery or antiestrogen therapy. We will be discussing the pathogenesis, histological findings, and treatment options of this rare condition. Our case is unique because BML in general do not tend to spread to multiple organs and tend to be limited to one site of disease.